Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content: 1. Disutopian Manifestations in the Algerian Novel: A Case Study "Watan Men Zojaj, A Fragile Homeland" Mrs. Fareda Jmea’an Alkrenawi 2. Deconstructive principles of Jacques Derrida Co-Prof. Hanadi Muhammad Behairi 3. The Usage: A Historical Analytical Study Dr. Rana Aniss Bleik 4. Linguistic Patterns’ Role in Arabic -Chinese Translation Lao Lingling 5. The syntactic preferences of Mohieddin Darwish in his book "Explanation and Explanation of the Qur’an" Dr. Jahangir Amiri, Mr. Salah Mohsin Hazim Al-Rawwas , Mr. Mohamed Zaher Abdel Mohsin Al-Anbaki 6. The grammatical embed phenomena in The Holy Quran Dr. Abdelrahman Mudawi Abdelrahim Alhadi, Mrs. Aysha Mohammed Abdu Allah Alhammadi 7. The effect of the morphological structure in determining the function of the grammatical phenomenon and its interpretation Dr. Ahmad Hilal Al-Salaymeh 8. Al-Dhafiri al-Yamani’s position on Ibn Al-Hajib’s opinions in his book Al-Manahil AI-Safia to revealing the healing meanings Mrs. Amani Zaid Ali Al-Shalili , Prof. Hadi Abdulla Naji Shamsan